2022
DOI: 10.1177/14673584221141301
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the business model canvas of the camping industry using cluster analysis

Abstract: Private and public camping businesses are struggling with the strategic and operational management of their establishments. Current research on the camping sector is scarce, whether related to campsite management or existing business models. This paper aims to identify the groups of business models in the camping industry, categorize camping businesses, and enable a better understanding of the factors distinguishing the different business models by proposing key financial and non-financial indicators. Thus, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In tourism studies, for example, researchers have utilized the BMC to analyze and understand the dynamics of tourism destinations, hospitality businesses, and tourist ex-periences. For example, scholars such as Grande and Camprubi (2024) [37], Kabil et al (2023) [38], Zoumpoulidis et al (2021) [39], and Strulak-Wójcikiewicz et al (2020) [40] have employed the BMC to map out key elements such as customer segments, value propositions, and revenue streams. Through their research, they identified opportunities for innovation, optimization, and sustainable growth within various sectors of the tourism industry.…”
Section: Strategic Role Of the Business Model In Saudi Medical And We...mentioning
confidence: 99%
“…In tourism studies, for example, researchers have utilized the BMC to analyze and understand the dynamics of tourism destinations, hospitality businesses, and tourist ex-periences. For example, scholars such as Grande and Camprubi (2024) [37], Kabil et al (2023) [38], Zoumpoulidis et al (2021) [39], and Strulak-Wójcikiewicz et al (2020) [40] have employed the BMC to map out key elements such as customer segments, value propositions, and revenue streams. Through their research, they identified opportunities for innovation, optimization, and sustainable growth within various sectors of the tourism industry.…”
Section: Strategic Role Of the Business Model In Saudi Medical And We...mentioning
confidence: 99%
“…The camping industry has positioned itself as an alternative form of accommodation (Brooker and Joppe, 2013; Salo et al, 2020; Grande and Camprubi, 2022) and, for some European destinations like France, has become the economic pillar of the hospitality sector (Grande and Camprubi, 2022; Eurostat, 2019). Europe is the second largest region in the world accounting for 27% of the global market in terms of capacity.…”
Section: Introductionmentioning
confidence: 99%